Effect of combined ultra-high pressure gallic acid cochromism on the stability of Aronia melanocarpa anthocyanins in juice systems - Jin Zhao; Shiqi Zhao; Yining Wang; Chuang Ma; Jinlong Tian; Aide Wang; Bin Li (Food Chemistry: X, 2025)
Aronia melanocarpa, a deciduous shrub of the Rosaceae family, produces fruits rich in anthocyanins which is well known for its strong antioxidant activity. However, the stability of anthocyanins in aronia juice is compromised by factors such as light, temperature, and pH, which can lead to discoloration. This study examined the effects of ultra-high pressure treatment combined with gallic acid on anthocyanin stability in aronia juice. These results indicated that the combined treatment significantly slowed discoloration and improved anthocyanin stability during storage. Metabolomic analysis identified the key anthocyanin glycosides cyanidin, peonidin, pelargonidin, and delphinidin, with significant differences in composition and content among the sample groups. Notably, cyanidin and pelargonidin levels were higher in the combined treatment, resulting in a more vibrant purple color. Multispectral methods and molecular dynamics simulations suggest that under ultra-high pressure with gallic acid, anthocyanins formed molecular clusters through π–π interactions, enhancing hydrogen bond stability with surrounding water molecules. This mechanism reduced the degradation and discoloration of anthocyanins during storage. This study provided valuable insights into the co-coloring effects of ultra-high pressure and phenolic acids on anthocyanin-rich juices.